PENGUATAN PENCEGAHAN STUNTING MELALUI PEMBERDAYAAN KADER MENGGUNAKAN MEDIA KALENDER EMAS DI DESA SUNGAI TUAN ULU - Pusparina, Iis; Ikasari, Filia Sofiani (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting is still a health problem in Indonesia. Posyandu as an extension of the community health center has cadres who act as the main spearhead of stunting prevention in the community. One effort that can be made to prevent stunting is to empower cadres. Empowerment can start by increasing cadres' knowledge about stunting. Many media can be used to transfer knowledge. One effective media based on the results of the service's research is using the EMAS Calendar (Education on the Problems of Stunting Children). Therefore, the activities carried out in community service take the form of empowering cadres through providing stunting prevention education using the EMAS calendar media. This community service aims to prevent stunting by empowering posyandu cadres using the EMAS calendar. The service method was by providing education to posyandu cadres using the EMAS calendar, then discussions and questions and answers. The result of this service activity was that all cadres said that their knowledge had increased about how to prevent stunting